Effect of one- vs. two-stair climb training on sprint power - Harris, K. B.; Brown, L. E.; Statler, T. A.; Noffal, G. J.; Bartolini, J. A. (The Journal of Strength and Conditioning Research, 2014)
Although running stairs is often used in sport conditioning programs, at present, little research has examined the effect of stair climb training on sprint power. The purpose of this study was to investigate the effects of running stairs either 1 stair (1S) or 2 stairs (2S) at a time on power. Fourteen male college track and field athletes were randomized into 3 groups; 1S, 2S, or control (C). All groups were pre- and posttested for 1S, 2S, and 40-m sprint split times. The 1S and 2S groups trained twice per week, for 4 weeks, performing 10 sets of climbing 68 total stairs with 2.5-minute rest between trials. The greatest power values (W) from pre- and poststairs and sprint splits were used for statistical analyses. There was a significant (p < 0.05) interaction of group × time for stair climb. The 1S group increased power for the 1S test (pre-1,492.89 ± 123.76; post-1,647.41 ± 73.65) with no change in the 2S test (pre-2,428.80 ± 414.81; post-2,430.32 ± 154.90), whereas the 2S group increased power for the 2S test (pre-2,343.73 ± 317.50; post-2,646.17 ± 305.43) with no change in the 1S test (pre-1,516.69 ± 210.64; post-1,529.38 ± 236.69). The C group showed no change in either stair test (1S: pre-1,403.35 ± 238.67, post-1,384.38 ± 153.32; 2S: pre-2,285.93 ± 345.03, post-2,261.85 ± 356.88). There were no significant interactions or main effects for any sprint split power (40 m: pre-5,337.13 ± 611.86, post-5,318.68 ± 586.24).Therefore, stair climb training either 1 or 2 at a time did not affect 40-m sprint split power but increased power for the specific stair training type. Coaches should choose the number of stairs that are similar in time and power output to sprint training.